The truth about the couch - Rubin, Adam, 1983-; Liniers, 1973- (New York : G.P. Putnam's Sons, 2024)
An imaginative account of the invention of the couch.
K-3
AD540L
Keywords: Sofas -- Fiction; Sofas -- Juvenile fiction; Humorous stories